Clay Components in Soil Dictate Environmental Stability and Bioavailability of Cervid Prions in Mice - Wyckoff, A. Christy; Kane, Sarah; Lockwood, Krista; Seligman, Jeff; Michel, Brady; Hill, Dana; Ortega, Aimee; Mangalea, Mihnea R.; Telling, Glenn C.; Miller, Michael W.; Vercauteren, Kurt; Zabel, Mark D. (Frontiers in Microbiology, 2016)
Chronic wasting disease affects cervids and is the only known prion disease to affect free-ranging wildlife populations. CWD spread continues unabated, and exact mechanisms of its seemingly facile spread among deer and elk across landscapes in North America remain elusive. Here we confirm that naturally contaminated soil contains infectious CWD prions that can be transmitted to susceptible model organisms. We show that smectite clay content of soil potentiates prion binding capacity of different soil types from CWD endemic and non-endemic areas, likely contributing to environmental stability of bound prions. The smectite clay montmorillonite (Mte) increased prion retention and bioavailability in vivo. Trafficking experiments in live animals fed bound and unbound prions showed that mice retained significantly more Mte-bound than unbound prions. Mte promoted rapid uptake of prions from the stomach to the intestines via enterocytes and M cells, and then to macrophages and eventually CD21+ B cells in Peyer’s patches and spleens. These results confirm clay components in soil as an important vector in CWD transmission at both environmental and organismal levels.□